Experimentally exploring nano-fluid of GnPs enriched waste coconut oil effects in cutting zone temperature reduction in motor shaft manufacturing process. (2022) - Senthilkumar, R.; Saravanan, R.; Maran, M.; Rajesh, S.; Raja, S.; Nagarathi, D.K.
Abstract: The machinability in term of Heat affected zone temperature is often considered due to surface properties modified by heat generated while machining. The control of such temperature is a prime importance. Here waste coconut oil (used one) from Kerala chips shop is used for lubricating purpose for machining the precision shaft. This piece of research work investigating the effect of Nano fluid of Nano GnPs powder concentrated used coconut oil (Waste) as coolant to upkeep the machining temperature at tool and work interface. The sensitive process variables like depth of cut, speed of cutting and feed rates were considered at four different level of settings. As this investigation involves 4 variables at four levels inputs. The Taguchi L16 orthogonal array employed commonly for designing the experiments for the cases of dry machining and nanofluid based wet machining. The t -test, Taguchi analysis and ANOVA conducted. It is found that the proposed method shows significant results than conventional dry machining. That is the proposed machining reduced the mean Cutting zone temperature significantly by 60 °C. The machining parameters optimized and studied the factors and influences at various levels. Based on the out come the proposed method recommended to process the SAE 1045 material for shaft manufacturing. As R 2 value found 99.16% R 2 95%) the predicted value with use of developed mathematical model has good agreement with the experimented results.